Reduction and melting behaviours of carbon – iron oxide composite using iron carbides and free carbon obtained by vapour deposition - R Higashi; D Maruoka; Y Iwami; T Murakami (The Australasian Institute of Mining and Metallurgy, 2024)
The ironmaking industry consumes a large amount of fossil fuel derived carbon as heat source, reducing agent of iron ores and carburising agent of reduced iron. Although the demand for drastic decrease of carbon dioxide emission, carbon is an essential element for smelting process of molten iron. The carbon recycling ironmaking process by circulating CO has been already proposed to achieve carbon neutrality. However, the production of molten hot metal is not considered in this process because sufficient amount of carbon does not dissolve in reduced iron by CO. Therefore, our group has suggested a new carbon recycling ironmaking process which can produce hot metal. In this process, free carbon and iron carbides produced by carbon deposition reaction using metallic iron as a catalyst are used. It is known that only Fe3C is obtained as iron carbide by using CO gas, however, Fe5C2 is also produced by adding H2 gas. The composite agglomerated with these carbonaceous materials and fine iron ore (Deposited Carbon-Iron oxide Composite: DCIC) is reduced and melted in a furnace. It is reported that Fe3C in DCIC accelerates the reduction reaction and melting of the composite. In this study, the effects of iron carbides and free carbon on the melting behaviour of DCIC are investigated. Fe3C, Fe5C2 and free carbon were produced by vapour deposition using porous iron whiskers and CO-CO2-H2 gas. These were agglomerated with hematite reagent at a certain ratio to prepare DCIC samples with and without Fe5C2. The samples were heated up to 1300°C in inert atmosphere. The DCIC containing Fe5C2 completely melted and iron nuggets were obtained after the experiment. This behaviour was not observed in the composite without Fe5C2. This indicates that using Fe5C2 is more preferable than Fe3C for molten iron production using DCIC.